NGHIÊN CỨU HIỆU ỨNG TĂNG CƯỜNG CHIẾT CỦA CÁC NGUYÊN TỐ ĐẤT HIẾM NẶNG (Gd, Tb, Dy, Ho, Er) BẰNG HỖN HỢP TRIPHENYLPHOTPHIN OXIT (TPPO) VÀ AXIT 2–ETYL HEXYL 2-ETYL HEXYL PHOTPHONIC (PC88A) Từ DUNG DỊCH AXIT NITRIC - Nhiệm, Đào Ngọc (Vietnam Journal of Chemistry, 2012)
The extraction of heavy rare earth elements  (Gd, Tb, Dy, Ho, Er) by mixture of triphenylphosphin oxide and 2-ethylhexyl 2-ethylhexyl phosphonic acid from nitric acid solutions has been developed. The influence of various factors such as the nitric acid concentration,  triphenylphosphin oxide concentration, 2-ethylhexyl 2-ethylhexyl phosphonic acid concentration, triphenylphosphin oxide /2-ethylhexyl 2-ethylhexyl phosphonic acid ratio,.. . on the Sk has been reported.